Association between alcohol use and violence-related injury in emergency department patients in Moshi, Tanzania: analysis of a prospective trauma registry - Kaitlyn Friedman, MScGH; Julius Raymond; Mary Catherine Minnig; Francis Sakita, MD; Joao Ricardo Nickenig Vissoci, PhD; Catherine Staton, MD (Elsevier, 2020)
Background: Harmful and hazardous alcohol use and violence are major contributors to global mortality and morbidity, despite being both predictable and preventable. This study seeks to quantify the association between violence-related injury and alcohol use disorders in a referral hospital in Moshi, Tanzania using a prospective trauma registry. Methods: We included all adult trauma patients (>17 years of age) presenting to the Kilimanjaro Christian Medical Center in Moshi, Tanzania in the registry. The trauma registry is an extensive instrument that was translated and back-translated from English to Kiswahili by local research assistants. The registry includes demographic information, patient history, clinical diagnosis and treatment, injury and surgery information, the Patient Health Questionnaire-2 (PHQ2), a behavioural health assessment, the Alcohol Use Disorders Identification Test (AUDIT), and substance use screening. An AUDIT score of ≥8 indicates harmful alcohol use in this setting. Alcohol use in the 6 h prior before injury was determined either from self-report or a blood alcohol concentration above 0. Category of injury (violence or non-violence) was self-reported. Findings: We included data from 500 patients enrolled in the trauma registry between April 17, 2018, and Jan 12, 2019. Of these, 84 patients (16·8%) reported that their injury was due to violence. Patients with violence-related injuries were 2·21 times more likely to have a positive alcohol status than were patients who presented with injuries not related to violence (95% CI 1·36-3·60; p<0·01). Among patients with violence-related injuries, those with a positive alcohol status were 6·26 times more likely to have an AUDIT score ≥8 than were patients with a negative alcohol status (95% CI 2·13-18·39; p<0·001). Interpretation: Alcohol use and violence-related injury pose a significant threat to health and wellbeing globally. In Moshi, Tanzania, both issues are prevalent and contribute to the burden of injury. To adequately reduce violence-related injuries in this setting, it is necessary to address harmful alcohol use. Funding: Fogarty International Center of the National Institutes of Health under Award Number K01TW010000 (PI, Staton) and the Duke Global Health Institute.